(untitled) (IUBAT Review, 2022)
The COVID-19 outbreak poses challenges for organizations as many external environmental objects are changing. It raises the importance of Human resource management (HRM) strategy as the HRM strategy works to motivate the employees and develops the workforce. The methodology used in this research is general literature review which shows the analysis of most recent articles, research papers and scientific study. The aim of this research is to identify HRM activities during COVID-19 pandemic and the way HRM develops their strategy to match their strategy with the organizational strategy to shove the business towards their goals. In the light of COVID-19, employee anxiety is increasing due to the deterioration of economic conditions, as well as an increase in the unemployment rate, and the number of businesses is congested. COVID-19 pandemic situation modify the Organizational strategy and HR strategy, and organizational critical goals are transform by COVID-19 pandemic situation. IUBAT Review—A Multidisciplinary Academic Journal, 5 (1): 44-53